Los microvertebrados (anfibios, reptiles y mamíferos) asociados al yacimiento de la Edad del Bronce de La Balsa la Tamariz (Tauste,Zaragoza) - Cuenca Bescos, Gloria; Laplana Conesa, César (Coloquios de Paleontología, 1995)
Ehe archaeological site Balsa la Tamariz (Bronze Age) hasa peculiar síructuje of 5 type.s of irchacologícal remains («hoyos»): human burials, stores, silo, rubbish durnp and human occupational structures. ihe faunal rcmains in hurials suggested a cultural sings o (le Pal eon tolog la. Faemí 1 tad de Ci e nc as. U oh-ers i dad d e Zaragoza, 5 <)t it >9 Depa rt.a ni e nl Zaragoza. 56 C. Laplana Cone a y G. Cuenca Bescos for sorne of the small vertebrates but the study of 0w fauna show no relatiousliip between man and animals. This study shows that the sinaí1 vertebrates are somewhat later to the human burjals and activities. They are amphibians: Bufo calamita, Pelobates cultripes; reptiles: Malpolon monspessulanus, Lacerta lepida; and maminals: Eliomys quercinus, Apodemus sp., Leporidae indet. Wc analize the siages in the formation and modification of small vertebrates bones assemblages and wc made an approach to te enviroument during or short after the human activities.